Human metapneumovirus uses endocytosis pathway for host cell entry. Issue 4 (August 2016) - Yang, Hui; He, Hao; Tan, Bin; Liu, Enmei; Zhao, Xiaodong; Zhao, Yao
Abstract: Human metapneumovirus (hMPV) is a prevalent pathogen worldwide and causes various respiratory infections. Although it is a critical pathogen in pediatric patients, it is unclear how it enters host cells. In this study, we focused on hMPV cell entry using two kinds of cell lines (Vero E6 and LLC-MK2), which are most commonly used for isolating and propagating for hMPV, and we used fluorescent dyes to label the virus particles and monitored how they enter the host cell in real time. We found that endocytosis was the predominant pathway by which hMPV entered host cells. When the virus particles were traced inside host cells, we found that a low intracellular pH was needed for intracellular fusion in LLC-MK2 cells. Highlights: A series of fluorescence methods were used to analyze hMPV viral entry. Endocytosis is proved the predominant pathway by which hMPV mediates to enter Vero E6 and LLC-MK2 cells. Fusion events occur intracellularly after hMPV being endocytosed. A low pH takes part in hMPV viral entry when it infects LLC-MK2 cells.